'n Ondersoek van performance-kuns in terme van metaskilderkuns en antiteatraliteit - Allen-Spies, J. (University of the Free State, 2009)
This comprehensive research project comprises an exploration of performance art in terms of meta-painting and antitheatricality and consists of two parts: a theoretical account and studio research. The two components are integral parts of the same investigation. In this research project I used a reciprical explorative process where both theoretical and visual research components conceptually and creatively interelate. Meta-painting is a performance of the nature of painting and visual representation. The characteristics of meta-painting or meta-representation derive from W J T 'Mitchell's concept of metapictures. He distinguishes three types - the picture that reflects the production of the picture; the picture within which another picture is recontextualised; the picture that reflects on picturality through its placement within a discursive frame. The concept of antitheatricality derives from Michael Fried's theory that an artwork is anti theatrical when there is complete identification between the subject pictured in an image and the activity represented. On the one hand, an artwork is said to be antitheatrical when it appears as if the figures represented in it are unaware of, or independent from, the spectator; the artwork does not "act" for an audience. On the other hand, the denial of spectatorship through a picture's metaphorical turning of its back on the spectator is a conscious, even theatrical action; the picture "acts" unaware. The relationship between theatricality and anti theatricality, or selfawareness and unawareness is therefore essentially dialectical. Antitheatrical meta-paintings are dialectically performative - their performativity entails self-awareness and self-referentiality, which is achieved through the apparent cancelling of spectatorship. Performativity in this thesis refers to artworks that appear self-aware of their own coming to be, as well as to performative actions that are not only represented, but that are also inherent in an artwork in terms of representation and medium. Moreover, it is possible to intertwine performance art, meta-painting and antitheatricality because performativity forms the basis of the discussions, constructions and deconstructions of pertinent artworks. Throughout the thesis emphasis is placed on art as involving a mediation of dynamic, performative actions between artist, artwork and spectator. Affinities between meta-painting and performance art are considered on the basis of the performative character of specific artworks or actions. On the basis of the performative nature of their self-reflexive and allegorical mediation on their function in the world as dialectical, self-denying objects or images, seventeenth century vanitas still life paintings are explored as special examples of meta-paintings. The allegorical reference to something other than what is represented is an example of performativity that is at stake in performance art as well as in photography. The discussion of photography as allegory of death by amongst others Roland Barthes and Gerhard Schoeman, in a manner that lends an element of vanitas to photographs, serves as supplement to the discussion of meta-painting and performance art. The affinity between performance art and meta-painting is explored further with regards to a performative, internalised iconoc1ash - resembling both iconophobia and iconophilia. Iconoc1ash here involves an image's simultaneous meta-representational and self-reflexive construction and deconstruction, vitalising and self-critical selfdestruction. Time (in terms of transience and passage) and space (in terms of the space that is made visible within an artwork through iconoc1ash and the dialectical, performative action between spectator and artwork) serve as catalysts for the performance or affirmation of internal iconoclash. The dialectics of anti theatricality in performance art and meta-paintings is discussed and highlighted throughout the thesis. Visibility and invisibility, presence and, absence, appearance and disappearance are shown to be mutual characteristics of the operation of antitheatricality. The boundary between performance art and metapainting is transcended through these mutual characteristics that flow from the dialectics of theatricality and antitheatricality, self-awareness and unawareness, acting and not acting.

My oorhoofse navorsingsprojek behels 'n ondersoek van performance-kuns in terme van metaskilderkuns en antiteatraliteit en bestaan uit twee dele; 'n teoretiese verslag en ateljeenavorsing in die vorm van 'n uitstalling. Die twee afdelings is integrale dele van dieselfde ondersoek. Metaskilderkuns vertoon die aard van skilderkuns en visuele representasie. Die eienskappe van metaskilderkuns of -representasie word gebaseer op WJT Mitchell se konsep en onderskeiding van drie verskillende soorte metaprente - die prent as 'n herhaling en refleksie van die produksie van die kunswerk; die prent waarbinne 'n ander prent geherkontekstualiseer word; die prent wat binne 'n diskursiewe raamwerk reflekteer op pikturaliteit. Die konsep van antiteatraliteit is gebaseer op Michael Fried se teorie dat 'n kunswerk antiteatraal is wanneer daar 'n algehele identifikasie is van die voorgestelde subjek in die skildery met die rol of aktiwiteit wat verbeeld word. Dialektiek tussen teatraliteit en antiteatraliteit ontstaan aan die een kant wanneer dit voorkom asof voorgestelde figure in 'n kunswerk onafhanklik of onbewus is van betragters; die kunswerk "tree nie op" vir betragters nie. Aan die ander kant is die ontkenning van betragterskap deur die kunswerk wat metafories gesproke sy rug op die betragter draai, 'n doelbewuste en selfs teatrale handeling; die kunswerk vertolk 'n rol van skynbare onbewustheid. Die verhouding tussen teatraliteit en antiteatraliteit, of selfbewustheid en onbewustheid is dus essensiëel dialekties. Antiteatrale metaskilderkuns IS dialekties performatief van aard - die performatiwiteit behels selfbewustheid en selfrefleksiwiteit wat verkry word deur die skynbare kanselering van betragterskap. Die performatiwiteit in hierdie verhandeling hou in die algemeen verband met kunswerke wat selfbewustheid van hulle eie bestaan suggereer, en spesifiek performatiewe handelinge wat nie net uitgebeeld is nie, maar wat ook by wyse van representasie asook medium inherent is aan die kunswerk of - aksie self. Deur performatiwiteit as basis VIr die besprekings, konstruksies en dekonstruksies van toepaslike kunswerke te aanvaar, is dit moontlik om samehangende verwantskappe en vervlegting tussen performance-kuns, metaskilderkuns en antiteatraliteit te bedink. Die kunsmedium as bemiddeling van die dinamiese, performatiewe interaksies tussen kunstenaar, kunswerk en toeskouer word deurentyds beklemtoon. Verwantskappe tussen metaskilderkuns en performance-kuns word op grond van die besondere performatiewe karakter van spesifieke kunswerke of handelinge ondersoek. Vanitas-stilleweskilderye word as gespesialiseerde metaskilderye ondersoek, aangesien hul selfrefleksiwiteit omtrent hul funksionering in die wêreld as dialektiese objekte of beelde en hul allegoriese karakter as performatief van aard verstaan kan word. Die allegoriese verwysing na iets anders as wat voorgestel word, is 'n voorbeeld van performatiwiteit wat in beide performance-kuns en fotografie ter sprake is. Fotografie wat deur onder andere Roland Barthes en Gerhard Schoeman as 'n allegorie van die dood beskryf word en wat dus ook vanitas-kenmerke besit, word as 'n aanvullende konsep van metaskilderkuns en performance-kuns bespreek. Die verwantskap tussen performance-kuns en metaskilderkuns word verder ondersoek aan die hand van performatiewe, geïnternaliseerde beeldestryd. Die beeldestryd is gebaseer op die idee van "iconoclash" wat die gelyktydige voorkoms van ikonophobia en ikonophilia is. Die beeldestryd behels dat kunswerke kan dui op 'n metarepresentatiewe en selfrefleksiewe konstruksie en dekonstruksie, verlewendiging en selfkritiek en/of afbreekproses. Tydelikheid (in die sin van tydsverloop) en ruimtelikheid (in die sin van die gelyktydigheid van die aksies van die beeldestryd en van die performatiewe handeling tussen betragter en kunswerk) bemiddel en aktiveer dan die beeldestryd intern en kontekstueel. Die dialektiek van antiteatraliteit in die behandelde voorbeelde van performance-kuns en metaskilderkunswerke word deurgaans bespreek en uitgelig. Sigbaarheid en onsigbaarheid, teenwoordigheid en afwesigheid, verskyning en verdwyning word as wedersydige eienskappe van die ontgrensende werking van antiteatraliteit uitgewys. Deur dié performatiewe eienskappe, as 'n uitvloeisel van die dialektiek tussen teatraliteit en antiteatraliteit, selfbewustheid en onbewustheid, vertoning en mevertoning, oorvleuel die velde van performance-kuns en metaskilderkuns.
Dissertation (M.A. (Fine Arts))--University of the Free State, 2009
Keywords: Performance art; Metacognition -- In art; Arts, Modern; Painting, Modern